PHYSICAL ACTIVITY BETWEEN STUDENTS FROM PUBLIC AND PRIVATE HIGH SCHOOL (Fiep Bulletin - online, 2012)
The aim of this study was on verifying the prevalence of physical activity between the genders with different economical conditions of young students in the city of Rio de Janeiro. It was selected 214 students from a private school (n = 100; age = 15, 7 ± 1,0) and from two public schools (n = 114; age = 16,4 ± 1,0). We used two questionnaires, one aiming on verify economical class and another on identifying gender, age, study place, physical activity participants and the reasons of the non-participants. After descriptive analyses, among the 214 subjects, 51% are physically active (PA) and 49% physically inactive (PI). The PA proportion reduces linearly while the economical class reduces the same for young men as for young women. The main reason for the inactivity was “lack of time” in both genders. The results indicated high level of PI between the young students, principally young women from a lower economical class.
Keywords: social class; physical activity; students